Cyanobacterial Harmful Bloom Lipopolysaccharides Induce Pro-Inflammatory Effects in Immune and Intestinal Epithelial Cells In Vitro - Skočková, Veronika; Vašíček, Ondřej; Sychrová, Eliška; Sovadinová, Iva; Babica, Pavel; Šindlerová, Lenka (Toxins, 2023)
Freshwater cyanobacterial harmful blooms (CyanoHABs) produce a variety of toxic and bioactive compounds including lipopolysaccharides (LPSs). The gastrointestinal tract can be exposed to them via contaminated water even during recreational activities. However, there is no evidence of an effect of CyanoHAB LPSs on intestinal cells. We isolated LPSs of four CyanoHABs dominated by different cyanobacterial species and LPSs of four laboratory cultures representing the respective dominant cyanobacterial genera. Two intestinal and one macrophage cell lines were used to detect in vitro pro-inflammatory activity of the LPS. All LPSs isolated from CyanoHABs and laboratory cultures induced cytokines production in at least one in vitro model, except for LPSs from the Microcystis PCC7806 culture. LPSs isolated from cyanobacteria showed unique migration patterns in SDS-PAGE that were qualitatively distinct from those of endotoxins from Gram-negative bacteria. There was no clear relationship between the biological activity of the LPS and the share of genomic DNA of Gram-negative bacteria in the respective biomass. Thus, the total share of Gram-negative bacteria, or the presence of Escherichia coli-like LPSs, did not explain the observed pro-inflammatory activities. The pro-inflammatory properties of environmental mixtures of LPSs from CyanoHABs indicate their human health hazards, and further attention should be given to their assessment and monitoring.
Keywords: sladká voda; Cyanobacteria; Microcystis; inflammation; macrophage; Endotoxins; lidé; Humans; cyanobacterial harmful bloom; Harmful Algal Bloom; sinice; Fresh Water; intestine; Lipopolysaccharides; lipopolysacharidy; cyanobacteria; lipopolysaccharide; endotoxiny; škodlivý vodní květ